AP16-OL7: A multilingual database for oriental languages and a language recognition baseline - Dong Wang; Lantian Li; Difei Tang; Qing Chen (2016 Asia-Pacific Signal and Information Processing Association Annual Summit and Conference (APSIPA), 2016)
We present the AP16-OL7 database which was released as the training and test data for the oriental language recognition (OLR) challenge on APSIPA 2016. Based on the database, a baseline system was constructed on the basis of the i-vector model. We report the baseline results evaluated in various metrics defined by the AP16-OLR evaluation plan and demonstrate that AP16-OL7 is a reasonable data resource for multilingual research.